Carotid intima media thickness versus plaque score: associations with stroke - Gazwa, Pitchou Zonga (My University, 2017)
Ischemic stroke caused by large artety occlusions for most cases of stroke. The majority of cases of ischemic stroke occurs as a consequence of thrombus formation, following rupture, erosion or calcification of atherosclerotic plaque. Conventional cardiovascular risk factors such as hypertension, diabetes mellitus, smoking, and dyslipidemia account for the large burden of stroke in South Africa.
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, for the degree of Master in Sciences (Medical), Johannesburg 2017
Keywords: Stroke; Carotid Intima-Media Thickness; Plaque, Atherosclerotic